Relationship between Antisocial Behavior and Parenting Style: A Case Study of Some Sampled Secondary Schools in Kisii County in Kenya - Michel, Kiarie O.; Anika, Alice A.; Lambert, Edward; Level, Rene T.; Islam, Mohammad Shahidul (European Journal of Applied Sciences, 2025)
Parenting style relates to the methods a person employs to raise their children. Most parents aren't aware of how their parenting style affects their children’s behavior. Parenting style is a contributing factor to children's antisocial behavior. The primary goal of this study was to investigate the relationship between parenting style and antisocial behavior in secondary school students. The study included students from public secondary schools in Kisii County. The study used a random sampling technique to select ten schools from Nyaribari Masaba Sub-County in Kisii. Two questionnaires, the Parental Authority Questionnaire (PAQ) and the Sub-Types of Antisocial Behavior (STAB), were used to collect data from 200 male (50 urban and 150 rural) and 150 female (50 urban and 100 rural) students. The Statistical Package for Social Sciences (SPSS) was used to analyze the data, and Pearson r was used to examine the data. The results showed that parents employed integrated parental style at varying degrees of permissive (M=2.75, S.D.=0.52), and authoritarian (M=3.19, S.D.=0.52) respectively. Students perceive mothers as authoritative in parenting style (M=3.22, S.D.=0.61) while fathers (M=3.27, S.D.=0.51). In conclusion, the two main factors that influence students to engage in antisocial behavior are permissive and authoritarian parenting approaches.